2019
DOI: 10.1007/jhep11(2019)150
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the top-quark mass in $$ t\overline{t} $$ + 1-jet events collected with the ATLAS detector in pp collisions at $$ \sqrt{s} $$ = 8 TeV

Abstract: A determination of the top-quark mass is presented using 20.2 fb −1 of 8 TeV proton-proton collision data produced by the Large Hadron Collider and collected by the ATLAS experiment. The normalised differential cross section of top-quark pair production in association with an energetic jet is measured in the lepton+jets final state and unfolded to parton and particle levels. The unfolded distribution at parton level can be described using next-to-leading-order QCD predictions in terms of either the top-quark p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 60 publications
10
51
1
Order By: Relevance
“…Good prospects for observing the exclusive signal over a mixture of inclusive and combinatorial background are achieved for all luminosity scenarios, although a good separation between the two is observed for rather low amounts of pileup, typically lower than hμi of 50. Statistical significances evaluated from estimated numbers of signal and background events are around 3 for the highest luminosity scenario ðhμi; L½fb −1 Þ ¼ ð50; 300Þ, about 6 for the (10,30) and 11 for the (5,10) scenarios. From a simple statistical analysis, we find that these significances are still not sufficient for a determination of the top quark mass that would be competitive with inclusive methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good prospects for observing the exclusive signal over a mixture of inclusive and combinatorial background are achieved for all luminosity scenarios, although a good separation between the two is observed for rather low amounts of pileup, typically lower than hμi of 50. Statistical significances evaluated from estimated numbers of signal and background events are around 3 for the highest luminosity scenario ðhμi; L½fb −1 Þ ¼ ð50; 300Þ, about 6 for the (10,30) and 11 for the (5,10) scenarios. From a simple statistical analysis, we find that these significances are still not sufficient for a determination of the top quark mass that would be competitive with inclusive methods.…”
Section: Discussionmentioning
confidence: 99%
“…This expectation is directly related to the fact that the top quark couples to all gauge bosons and the Higgs boson, which implies that the top production is very sensitive to the presence of BSM phenomena. In addition, recent experimental results for the inclusive top pair production have demonstrated that this process can be used to measure the top mass in a well-defined scheme with high accuracy [5][6][7][8][9][10]. These results provide motivation for the study of the top pair production in diffractive processes, where the final state is cleaner than the typical inclusive one, where both incident protons fragment and a large number of particles are produced in addition to the top pair (for a review on diffraction see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Precision theoretical predictions for this observable, especially in the threshold region, are therefore highly demanded to achieve the goal of extracting the top quark mass. A closely related observable ρ s (and similar ones) in tt + jet production was employed in [17][18][19][20][21], where ρ s is defined as…”
Section: Jhep06(2020)158mentioning
confidence: 99%
“…The recent measurements of the pole and MS mass of the top quark in proton-proton collisions are presented in Refs. [29,30].…”
Section: Perturbative Qcd and Renormalizationmentioning
confidence: 99%